Emerging Trends and Geographical Influences on Yoga: A Study of Yogic Practices - Shrestha, Suman Kumar; Adhikari, Sapana; Karky, Jant Raj; Timsina, Saroj Kumar (AMC Journal, 2024)
This study explores the complex interplay between geography and yoga, highlighting how geographical factors such as location, climate, and time of day influence yogic practices, and discusses the various ways in which these elements of place, climate, and time interlink with and impact the practice of yoga. The idea of yoga evolved from the very roots of Indus Saraswati Valley Civilization in order to integrate body, mind, and spirit into the environment to ensure well-being. The Sanskrit word "Yuj" means "to unite" and shows yoga's goal of balancing mind and body. Employing qualitative descriptive methods, including interviews, in Kerabari Municipality, Nepal, the research highlights the influence of geographical contexts on the practice and benefits of yoga. The concept of Yoga-Geography underscores yoga's adaptability across time and space, enhancing physical fitness, mental clarity, emotional stability, and educational harmony. The reviews of the history of yoga throughout five key periods: the Vedic period, which focused on spirituality around 3000–4000 BCE; the Pre-Classical period, which spoke of philosophical ideas in the Upanishads from 2000–1000 BCE; the Classical era, when Patanjali organized yoga into a system from 184–148 BCE; the Post-Classical period, which introduced practices like Tantra and Hatha Yoga from 800–1700 AD; and the Modern era, which saw yoga spread throughout the world from 1700 AD to the present. A blend of ancient tradition and the present world, yoga continues to foster personal and collective growth, environmental awareness, and well-being in general. The practice of yoga is influenced by the environment, with climates shaping whether people practice more active or relaxing postures, and time affecting whether sessions focus on energy or relaxation. Nepal’s spiritual traditions draw people looking for a traditional yoga experience. The research highlights how the climate influences different yoga asanas and how time of day affects the focus of yoga sessions. It also contrasts global yoga trends with Nepal's spiritual heritage, showing how yoga practices are interconnected with both cultural and environmental factors.